Understanding Diagnostic Delays for Kaposi Sarcoma in Kenya: A Qualitative Study. (15th August 2022) - McMahon, Devon E.; Chemtai, Linda; Grant, Merridy; Singh, Rhea; Semeere, Aggrey; Byakwaga, Helen; Laker-Oketta, Miriam; Maurer, Toby; Busakhala, Naftali; Martin, Jeffrey; Bassett, Ingrid V.; Butler, Lisa; et al.
Abstract : Background: Although HIV-associated Kaposi sarcoma (KS) is frequently diagnosed at an advanced stage in sub-Saharan Africa, reasons for diagnostic delays have not been well described. Methods: We enrolled patients >18 years with newly diagnosed KS between 2016 and 2019 into the parent study, based in western Kenya. We then purposively selected 30 participants with diversity of disease severity and geographic locations to participate in semistructured interviews. We used 2 behavioral models in developing the codebook for this analysis: situated Information, Motivation, and Behavior framework and Andersen model of total patient delay. We then analyzed the interviews using framework analysis. Results: The most common patient factors that delayed diagnosis were lack of KS awareness, seeking traditional treatments, lack of personal efficacy, lack of social support, and fear of cancer, skin biopsy, amputation, and HIV diagnosis. Health system factors that delayed diagnosis included previous negative health care interactions, incorrect diagnoses, lack of physical examination, delayed referral, and lack of tissue biopsy availability. Financial constraints were prominent barriers for patients to access and receive care. Facilitators for diagnosis included being part of an HIV care network, living near health facilities, trust in the health care system, desire to treat painful or disfiguring lesions, and social support. Conclusions: Lack of KS awareness among patients and providers, stigma surrounding diagnoses, and health system referral delays were barriers in reaching KS diagnosis. Improved public health campaigns, increased availability of biopsy and pathology facilities, and health provider training about KS are needed to improve early diagnosis of KS.